Significance of CD47 expression in endometrial carcinoma - Nurhan Sahin; Ganime Coban; Nurcan Unver; Dilek S Arici; Gokhan Kilic; Ozlem Toluk (Wolters Kluwer Medknow Publications, 2022)
Objectives: CD47 is a membrane protein that belongs to the immunoglobulin superfamily and regulates macrophage phagocytosis negatively. As CD47 expression at the cancer cell membrane would inhibit the phagocytic activity of immune cells, it is connected to an unfavorable prognosis in leukemia and malignancies of various solid organs. Materials and Methods: In this study, retrospectively evaluated 72 patients who had been diagnosed with endometrial carcinoma at Pathology Department and had undergone total abdominal hysterectomy and bilateral salpingo-oophorectomy (TAH + BSO) and/or lymphadenectomy. CD47 expression was evaluated in tumorous and nontumor areas in all patients considering cytoplasmic and membranous brown staining in cells. The proportion of expression was evaluated as well as the intensity and an "h score" was obtained. This score was compared with known prognostic parameters. Results: CD47 expressions showed a statistically significant correlation with tumor grade (P < 0.05); however, no significant relationship was observed with myometrial invasion depth and lymph vascular invasion status (P = 0.923 and P = 0.754, respectively). Conclusions: As with other tumors, anti-CD47 antibody may be an alternative treatment option in patients with high-grade endometrial carcinoma.